وسائل الدعاية السياسية السلبية والهجوم على المصلحين (رؤية قرآنية - إعالمية) = The means of political propaganda and the attack on the reformers (A Quranic – mass communication perespective) - Zaroum, AbdulHamid Mohamed Ali (Universiti Sultan Azlan Shah (USAS), 2019)
تعالج هذه الورقة خطورة التضليل الإعلامي الذي يمارسه أعداء الحق والصلاح، ضد دعاة الحق والصلاح والإصلاح والإرشاد في المجتمعات؛ وذلك بغية صرف الجماهير عنهم، والحيلولة دون وصول كلمة الحق إلى الخلق. محور هذه الدراسة وسائل الدعاية السلبية، والهجوم على الأنبياء والمصلحين، من منظور قرآني- إعلامي. ومن أهم وسائل الدعاية السلبية التي تعرض لها هذا البحث: الهجمة الإعلامية الشرسة التي تشنها القيادات المستكبرة ضد الأنبياء وأتباعهم، همـزا، ولمــزا، وتعـريـضا، وتشهيرا وتنفيرا للأتباع وإن لم يُجدِ كل ذلك نفعا، تحوّل الأمر إلى هجوم مباشر؛ ضربا، وتعذيبا، وتشريدا، وتقتيلا. ومن وسائل الدعاية السياسية التي توخى الباحث دراستها: المقارنة المباشرة التي يعقدها المستكبرون؛ لإثبات أحقيتهم بقيادة شعوبهم من جهة، وإثبات عدم أهلية الأنبياء والمصلحين للقيام بذلك من جهة أخرى، إضافة إلى المقارنة الضمنية. تم اتباع المنهج الاستقرائي التحليلي التاريخي المقارن. ومن بين ما توصلت إليه الدراسة أن الإعلام سلاح ذو حدّين، فقد كان وسيظل الفيصل في تزييف الحقائق، وتمييع القضايا الرئيسة للشعوب، وفي تعرية خبث المستبدّين، وكشف تلاعبهم بالعقول. إن االقرآن لا ينفك يدعو أتباعه إلى استخدام العقل، وعدم الانصياع إلى أقاويل المرجفين، وإشاعات المبطلين، وتهديدات المستبدّين المستكبرين. وقد سبق القرآن الكريم كل العلوم الحديثة، ومنها فن الإعلام، وعلم الاتصال، في تناوله لوسائل وأساليب الاتصال الجماهيري، والدعاية السياسية السلبية، والهجوم على الأنبياء والمصلحين. ************************************************************************************ This paper addresses the danger of disinformation and deception practice by the enemies of truth and righteousness, against the advocates of truth, righteousness, reform and guidance in societies, in order to dispel the masses from them and to prevent the public from knowing the truth. The focus of this study revolves around the means of negative propaganda, and the attack on the prophets and reformers, from the Quranic–communication perspectives. The most important means of negative publicity discussed in this research: the vicious media attack launched by the arrogant leaders against the prophets and their followers, be it in the form of slandering and backbiting or harassment, or intimidation or causing the aversion of the followers and if all of these were proven to be useful, it turned into a direct physical attack; beating, torture, and abhorrent. One of the means of political propaganda that the researcher intended to study: the direct comparison held by the overbearing political leaders to prove their right to lead their people on the one hand, and prove the incapacity of the prophets and reformers to do so on the other hand, in addition to the implicit comparison. Thus, comparative, historical and analytical methods have been used in this research. Among the findings of the study is that media is a double-edged sword; it would continue to falsify the facts, dilute the main issues of the people, expose the tyranny of tyrants, and expose their manipulation of the minds. The Qur’an continues to call upon its followers to use reason, not to obey the words of the ascetics, the rumors of the deceiver, and the threats of the arrogant tyrants. That is why we find The Holy Quran has preceded all modern sciences, including media and communication, in dealing with means and methods of mass communication, negative political propaganda, and attack on prophets and reformers.